Pengaruh Model Problem Based Learning (PBL) dan Project Based Learning (PjBL) Terhadap Hasil Belajar Biologi Pada Materi Pencemaran Lingkungan Siswa Sekolah Menengah Atas - Prihartini, Eka (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This research was aimed to determine: the effect of model problem based learning (PBL), project based learning (PjBL) and conventional learning to: biology learning outcomes of students in the matter of environmental pollution in SMA Negeri 2 Kota Tebingtinggi. A quasi-experiment research used pretest-posttest control group design. Samples were selected using random cluster sampling technique and divided into experiment and control classes. The tenth class of sains-2 was applied with conventional learning (control), the tenth class of sains-3 was applied with problem based learning (PBL), and the tenth class of sains-4 was applied with project based learning (PjBL). Data were analyzed using Analysis Covarian (anacova) at the level of significance Î± = 0.05 and followed by Tukeyâs test with SPSS ver 21.0. The results showed that: There was an effect of learning model to biology learning outcomes (P= 0,025). Biology learning outcomes that learned with problem based learning (81,46 Â± Â 6,59) was higher than the project based learning (81,43 Â± 10,14) and conventional learning (65,43 Â± 7,10). Based on the results showed that problem based learning (PBL) is better than project based learning (PjBL) and conventional learning.